An Investigation of the Asymmetric Impacts of the Thai Monetary Policy on the Real Estate Market - Chockpisansin, Kanjana; Sethapramote, Yuthana (Journal of Applied Economics and Management Strategy, 2024)
This paper’s objective is to investigate how monetary policy changes impact the housing loans and residential housing markets. To estimate the impulse response functions, the quarterly seasonally-adjusted times-series data during Q1/2000-Q2/2023 are utilized in both VAR and MS-VAR frameworks to explore whether the Thai housing loans and real estate markets have a unique reaction to the changes in monetary policy instruments or not. The two housing market variables, namely housing loans and house prices, the interest rate charged on housing loan contracts, as well as the Bank of Thailand’s policy rate, are included in the model as endogenous variables, while other three variables, namely the economic growth rate, headline inflation rate, and money supply growth rate, are also incorporated into the model as exogeneous variables. The empirical results from the MS-VAR model help clarify that there exist two different and independent states for the Thai housing market, resulting in asymmetric effects of monetary policy that are transmitted to the housing market. In addition, the monetary policy shock becomes significant and noticeable during the low-volatility period. Due to the existence of the nonlinear relationship among housing variables and the monetary policy instrument, the monetary authority should be cognizant of the negative impact of tightening monetary policy on the housing market. Furthermore, the traditional monetary policy instrument, the policy interest rate, may not be the most effective instruments for containing the overheated scenario in the housing and real estate markets.